Access to urban basic services and determinants of satisfaction: a comparison by non-slum and slum dwellers in Dhaka city - Islam, M. Shahidul; Khan, Mohammad Nasir Uddin (BRAC University, 2018)
IGS Working Paper Series No. 10/2013